Public Relations Management In Increasing Community Participation - Hadi, Rizal; Latif, Muhammad Sabri; Amin Nur, Muhammad; Firdausi Nuzula, Jannatul; Ulfaturrahmah (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2024)
This research aims to explore the effectiveness of planning, implementation and evaluation of community relations management (PR) in increasing community participation in MTsN Batu City using a qualitative approach with a case study method. Data collection techniques include participant observation, in-depth interviews, and documentation studies, which are analyzed using the Miles and Huberman model through a process of data reduction, data presentation, and verification. The research results show that public relations planning at MTsN Batu City is carried out systematically, including identifying needs, formulating program strategies, ongoing evaluation, and efficient allocation of funds. Public Relations implementation involves active participation of all institutional members, targeted communication, use of social media, regular publications, monitoring public opinion, and intensive outreach. Program evaluation is carried out regularly using various techniques to ensure comprehensive feedback. This research confirms the importance of the strategic role of Public Relations in increasing community participation and building a positive image of educational institutions, as well as providing practical recommendations for developing effective Public Relations management models for educational institutions in Indonesia to increase community participation in school activities and support the achievement of better educational goals.